Enhanced space vector modulated scalar control of induction motor - Ramana Vasu. R; George Fernandez S.; Vijayakumar K. (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A conventional vector control of the asynchronous machine makes an analogy of an equivalent separately excited DC machine. It offers a decoupled control of torque and flux which is perpendicular to each other hence one vector is not interfered by other parameters. So, torque and speed control is achieved in an isolated manner even though they are closely interlinked. This is implemented by aligning the rotor flux with the direct axis of the synchronously rotating reference frame. PI controllers play a key role to achieve the desired topology of the VFD. Three controllers are used in the system, flux, speed and torque controller. Tuning of flux controller is quite simple, but in case of speed and torque, it became quite tricky because the output of the speed controller is the reference signal of torque controller. Moreover, there is no distinct method to tune the controllers in the vector control system. Still, the entire high-performance dynamic response of the machine depends on the perfect tuning of those controllers. From the above analysis, it is understood that system identification is essential to tune the PI controllers. But being an asynchronous machine, to obtain system transfer function in a decoupled manner is very difficult. To overcome this problem, the proposed model will be Conventional sine PWM modulated switching pulses are used to implement variable frequency drives for induction motor. Space vector modulated PWM switching pulse is used to fire IGBT. In the case of sine, PWM modulated switching; DC bus voltage utilization is 50% whereas in space vector modulated inverter 57.73% DC Bus voltage utilization can be achieved.